Imigrantes e o mercado de trabalho no Brasil: segmentação entre brasileiros e estrangeiros e o impacto da língua materna - Machado, Renata Caixeta (2016)
Labor migration is at the center of contemporary economic regulation and suggests a demographic process that highlights the need for people mobility. In this sense, the understanding of manpower mobility is essential for the determination of immigration policies. The general objective of this study is to analyze immigrants reality in the Brazilian labor market from two perspectives: regarding the existence of segmentation between brazilians and foreigners; and in relation to the impact of the mother tongues on the insertion of the workers in the host society. For this, we use multinomial logit models. In the first place, we seek to verify the effect of the immigrant condition on the probabilities of the individual belonging to one of the proposed states of employment - inactivity, unemployment, primary and secondary occupation. Second, we try to evaluate if, how and to what extent certain characteristics of native languages of immigrants - latin origin, explicit distinction between genders and generic reference to the future - interfere in the probability of them finding themselves inactive, unemployed and occupied. Data from the 2010 Demographic Census, provided by the Brazilian Institute of Geography and Statistics (IBGE), are used for the country as a whole, and the sample is restricted to the Population in the Working Age (10 to 65 years). The results indicate that there is no segmentation between the internal and external workforce in Brazil, since the fact that being an immigrant increases his chances of working in a primary occupation and decreases the probability of entering a secondary occupation. In addition, it can be seen that the aforementioned characteristics of the languages spoken by immigrants exert an influence on the placement of immigrants in the Brazilian labor market. Specifically, the results show that persons who use latin languages have lower chances of being inactive and greater chances of being employed; women whose languages are gender-biased are more likely to be inactive; and those who speak weak FTR languages have reduced probability of unemployment. The present paper fills some gaps in the literature on immigration, especially in Brazil. It also contributes, as an additional research on the subject, and can thus support the formation of public policies focused on the international migratory flows destined to the Brazil.